Empowering Village Communities Through Mutual Cooperation Mobilization Agents in Kalimontang Village in Overcoming Stunting - Mujahidin; Lalu Ahmad Murdhani (International Journal of Scientific Research, 2024)
Stunting is a world problem because of its implications for determining the future of the nation. Indonesia, as a developing country, still has a high stunting prevalence rate. Based on data from the 2022 National Nutrition Status Survey (SSGI), the prevalence of stunting in Indonesia is 21.6%. This figure is still more than the target figure set by the World Health Organization (WHO), the stunting rate should be no more than 20%. There were obstacles in implementing the stunting reduction target, one of which was a lack of important intake such as animal protein and vegetable protein. This research was conducted with the aim of analyzing stunting prevention by empowering village communities through mutual cooperation agents in Kalimantong Village, West Sumbawa Regency. The research method uses a descriptive qualitative approach. The research results show that Kalimantong Village has a relatively low prevalence rate compared to other villages in Brang Ene District, West Sumbawa Regency. Therefore, to support the target of reducing stunting, human empowerment is needed through mutual cooperation agents to prevent stunting and increase human resources in Indonesia.